2023
DOI: 10.1108/apjml-11-2022-0959
|View full text |Cite
|
Sign up to set email alerts
|

The influence of event-related factors on sport fans' purchase intention: a study of sponsored products during televised sporting events

Abstract: PurposeIt is not possible for every fan of a sport to watch matches at stadiums because of the capacity and location constraints. Furthermore, although sport fans could not physically attend sporting events during the COVID-19 pandemic, corporations still showed interest in sponsoring such events. To better understand this phenomenon, this study examined the effects of fans' event involvement on event reputation, event commercialization, corporate brand credibility, corporate brand image and purchase intention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…The undertaken audience engagement and forms of promotion have benefited from marketing plans, which are based on big data technology and contemporary sports marketing theory (Chen, 2023). The presence of fans at televised sporting events has a beneficial effect on the event's reputation, corporate brand credibility, and image, as well as influences purchasing decisions (Rai et al, 2024). It has been found that having spectators at televised sports events produces benefits beyond the thrill of the moment.…”
Section: Promoting Sports Development Programmes and Increasing Sport...mentioning
confidence: 99%
“…The undertaken audience engagement and forms of promotion have benefited from marketing plans, which are based on big data technology and contemporary sports marketing theory (Chen, 2023). The presence of fans at televised sporting events has a beneficial effect on the event's reputation, corporate brand credibility, and image, as well as influences purchasing decisions (Rai et al, 2024). It has been found that having spectators at televised sports events produces benefits beyond the thrill of the moment.…”
Section: Promoting Sports Development Programmes and Increasing Sport...mentioning
confidence: 99%